Cardiac and lung endothelial cells in response to fluid shear stress on physiological matrix stiffness and composition. (29th September 2020) - Bacci, Cydnee; Wong, Vanessa; Barahona, Victor; Merna, Nick
Abstract: Objective: Preconditioning of endothelial cells from different vascular beds has potential value for re‐endothelialization and implantation of engineered tissues. Understanding how substrate stiffness and composition affects tissue‐specific cell response to shear stress will aid in successful endothelialization of engineered tissues. We developed a platform to test biomechanical and biochemical stimuli. Methods: A novel polydimethylsiloxane‐based parallel plate flow chamber enabled application of laminar fluid shear stress of 2 dynes/cm 2 for 12 hours to microvascular cardiac and lung endothelial cells cultured on cardiac and lung‐derived extracellular matrix. Optical imaging of cells was used to quantify cell changes in cell alignment. Analysis of integrin expression was performed using flow cytometry. Results: Application of fluid shear stress caused the greatest cell alignment in cardiac endothelial cells seeded on polystyrene and lung endothelial cells on polydimethylsiloxane. This resulted in elongation of the lung endothelial cells. αv and β3 integrin expression decreased after application of shear stress in both cell types. Conclusion: Substrate stiffness plays an important role in regulating tissue‐specific endothelial response to shear stress, which may be due to differences in their native microenvironments. Furthermore, cardiac and lung endothelial cell response to shear stress was significantly regulated by the type of coating used.